Plasma Neutrophil Gelatinase Associated Lipocalin In The Early Detection Of Acute Kidney Injury In Patients Undergoing Cardiac Surgery - ANUSHA R,; SANTHI SILAMBANAN,; MADHUBALA VEERASAMY, (International Journal of Pharma and Bio Sciences, 2015)
The aim of this study is to determine that plasma Neutrophil Gelatinase Associated Lipocalin (NGAL) detects AKI earlier in patients undergoing cardiac surgery compared to serum creatinine. It is a single centre, case control study, where 50 controls (apparently healthy individuals) and 53 cases (adults who underwent major cardiac surgeries) were chosen as study group. Plasma NGAL and serum creatinine were estimated in random samples for controls. NGAL was estimated preoperatively and at 4 hours post operatively for the study group. Creatinine was estimated preoperatively and at 4 hours, 24 hours, 48 hours and 72 hours post operatively for the study group. Plasma NGAL was measured using ELISA and creatinine using modified kinetic Jaffe method. Paired T test was used to analyse different variables. NGAL post operative values at 4 hours were higher than the NGAL pre operative values (p=0.00). Creatinine post operative values at 4 hours (p=0.28) and 24 hours (p=0.30) were not higher whereas at 48 hours (p=0.04) and 72 hours (p=0.01) were higher. Among the 53 patients, 13 were classified as AKI based on AKIN criteria. Creatinine levels were elevated at 48 hours and NGAL levels were elevated at 4 hours in patients with AKI. NGAL was increased at 4 hours and creatinine at 48 hours in patients with AKI, indicating NGAL can detect AKI earlier compared to creatinine